The Science of Citizen Science 2021
DOI: 10.1007/978-3-030-58278-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Data Quality in Citizen Science

Abstract: This chapter discusses the broad and complex topic of data quality in citizen science – a contested arena because different projects and stakeholders aspire to different levels of data accuracy. In this chapter, we consider how we ensure the validity and reliability of data generated by citizen scientists and citizen science projects. We show that this is an essential methodological question that has emerged within a highly contested field in recent years. Data quality means different things to different stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 60 publications
0
61
0
Order By: Relevance
“…The numerous examples of using data mining in citizen science projects include but are not limited to astronomy, life sciences, environmental sciences and oceanography (Franzen et al, 2021). While citizen science offers enormous opportunities, for example in training classification algorithms, there is also a need for rigorous procedures to ensure data quality (Balázs et al, 2021), as in any scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…The numerous examples of using data mining in citizen science projects include but are not limited to astronomy, life sciences, environmental sciences and oceanography (Franzen et al, 2021). While citizen science offers enormous opportunities, for example in training classification algorithms, there is also a need for rigorous procedures to ensure data quality (Balázs et al, 2021), as in any scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings draw attention to the necessity of an alignment between trainers before delivering workshops for general participants. Promoting continuous data quality assessment through the initiative (Balázs et al, 2021) is important to achieve robust data (Bonter and Cooper, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the low response rate in the validation process (around 11%), along with the restricted number of participants who engaged in the monitoring days after the workshop, it is clear that interest or engagement with the initiative's goals is a limiting factor. Perhaps a possibility to have more participants involved in the validation process is to keep participants informed (and reminded) of the importance of this procedure for the applicability of the outcomes (Balázs et al, 2021). Also, it has been shown that communication about the application of the data gathered is fundamental to maintain participants engaged and interested (Schläppy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Their supply and use can be expected to expand rapidly in the coming years, but this will require solutions to overcome issues around quality control and validation (Balázs et al, 2021;Wiggins et al, 2021. ) In the agriculture and food domain, crowdsourced data are more common in price data collection efforts, where agents or volunteers can be recruited to survey markets (UN Global Pulse, 2015; Zeug et al, 2017;Ochieng and Baulch, 2020).…”
Section: Crowdsourced and Citizen-generated Datamentioning
confidence: 99%